Rotating electric machinery and transformer technology - Richardson, Donald V. (Prenctice Hall, 1997)
This book fills the need for an up-to-date source of information on how to connect, operate, adjust, and take performance data on the entire field of electric machinery. It enables readers to recognize, understand, analyze, specify, connect, control and effectively apply the various existing types of electric motors and generators.